Kendala Provider Dan User Dalam Memanfaatkan Program Pelayanan Kegawatdaruratan Public Safety Center (PSC) 119 Di Kabupaten Tabanan - I Putu Eka Viqtrayana (STIKES ADVAITA MEDIKA TABANAN, 2021)
Abstract Background: Emergency conditions cannot be predicted at any time and require immediate help, so PSC 119 emergency services are here to help when handling victims, save lives, improve emergency services, and prevent them. After less than two years of implementing the Tabanan Serasi PSC 119 program, there are still many people in Tabanan Regency who do not know for sure about the existing PSC 119 services. Objective: This study aims to determine the constraints of providers and users in utilizing the PSC 119 emergency service program in Tabanan Regency. Methods: This study used a qualitative research design with an exploratory approach. This research was conducted in Unit PSC 119 of the Tabanan District Health Office in June-July 2020. The research data were analyzed using thematic methods. Data were collected through observation of the implementation, tracing documents and exploring 12 informants. Two main informants as providers are coordinator and implementer. Ten supporting informants as users, namely the community has not and have used it. Results: The results showed that the use of PSC 119 in emergency services from providers/managers were, lack of procurement of infrastructure, human resource constraints, program structure position, round table, not yet utilizing call center 119, PSC operators lack of coordination with PSC 119 network. , do not have radiomedical equipment, and lack of monitoring and evaluation. Constraints from users/communities are contacting the 119 call center, public knowledge about PSC 119 services, and outreach activities. Strategies to overcome obstacles are to propose priorities according to the priority scale, seek human resources, seek infrastructure; training for implementing officers; implementation monitoring and evaluation; create innovation services; and socialize to the community about the program. Conclusion: There are several obstacles to the use of PSC 119 in emergency services, both from providers/managers and users/communities, so the advice obtained is that the program manager continues to socialize, utilize existing personnel and make service innovations. The Tabanan District Health Office is expected to facilitate the implementation, carry out monitoring and evaluation of the PSC 119 program every year and improve the development and facilitate the program proposing PSC 119 to become a Technical Implementing Unit.